‘Notes on a Scandal’: Why do Females Engage in Abuse of Trust Behaviours? - Darling, Andrea J.; Antonopoulos, Georgios A. (International Journal of Criminology and Sociology, 2013)
Although an evident reality in organisations where females work with young people, there has been no specific research to date exploring why females in positions of trust engage in sexually abusive relationships with adolescents. This study investigated the subject through a qualitative analysis of ten case studies from England drawn from the employment and safeguarding environment, comparing findings with existing studies into female sexual offenders in general, research into male ‘professional perpetrators’ and Gannon et al.’s (2008) Descriptive Model of Female Sexual Offending. The research highlighted a number of key similarities and differences between those who abuse in positions of trust and those female sexual offenders who abuse children in wider contexts. With respect to etiological factors the similarities included unstable lifestyle, relationship difficulties, low self-esteem, cognitive distortions and emotional self-management problems. Motivations for this sample appeared to be primarily driven by intimacy needs. Differences were identified relating to lower levels of substance abuse, a higher age range and socio-economic status, less prevalence of severe social skills deficits and chaotic and abusive backgrounds in this subject group. All of the women in the study followed an Implicit Disorganised pathway of abuse and maternal approach to the abusive behaviour.